Mapping indicators in African NAPs and NDCs. - Njuguna, Lucy; Nowak, Andreea C.; Rosenstock, Todd (2024)
Following SB60, stakeholders were invited to submit information on existing indicators to the UNFCCC. This presentation shares findings from an analysis of tracking elements in African NAPs and NDCs, with a focus on adaptation indicators highlighting gaps and opportunities to consider while defining indicators for the Global Goal on Adaptation.